High Consumption Volatility : The Impact of Natural Disasters? - Auffret, Philippe (World Bank, Washington, DC, 2014)
A history of repeated external and domestic shocks has made economic insecurity a major concern across the Caribbean region. Of particular concern to all households, especially the poorest segments of the population, is the exposure to shocks that are generated by catastrophic events or natural disasters. The author shows that despite high consumption growth, the Caribbean region suffers from a high volatility of consumption that decreases household welfare. After presenting some empirical evidence that consumption volatility is higher in the Caribbean region than in the rest of the world, he makes some empirically testable inferences that help explain consumption volatility. The author develops a conceptual framework for analyzing the effects of catastrophic events on household and aggregate welfare. According to this framework, the volatility of consumption comes from production shocks that are transformed into consumption shocks mostly because of underdeveloped or ineffective risk-management mechanisms. Auffret conducts an empirical analysis of the impact of catastrophic events on 16 countries (6 from the Caribbean region and 10 from Latin America) from 1970-99 and shows that catastrophic events lead to: 1) A substantial decline in the growth of output. 2) A substantial decline in the growth of investment. 3) A more moderate decline in consumption growth (most of the decline is in private consumption, while public consumption declines moderately. 4) A worsening of the current account of the balance of payments.